CBS c.844ins68 Polymorphism Frequencies in Control Populations: Implications on Nonsyndromic Cleft Lip with or without Cleft Palate. (January 2015) - Murthy, Jyotsna; Lakkakula, Saikrishna; Gurramkonda, Venkatesh Babu; Pathapati, Ram Mohan; Maram, Rajasekhar; Lakkakula, Bhaskar
Introduction: Nonsyndromic cleft lip with or without cleft palate (NSCLP) is a common birth defect with substantial clinical and social impact. Folate deficiency is one of the factors that have been associated with increased risk for NSCLP. Polymorphisms in folate and homocysteine pathway genes may act as susceptibility factors. Objective: The objective of this study was to evaluate prevalence estimates of cystathionine beta-synthase (CBS) insertion of 68-bp (c.844ins68) polymorphisms and their correlation with NSCLP. Material and Methods: A total of 236 unrelated individuals from seven Indian populations and an additional 355 cases with NSCLP and 357 controls without NSCLP were included in this study. We investigated the CBS c.844ins68 polymorphism in all samples. Genotyping was performed with polymerase chain reaction and electrophoresis. The data were statistically analyzed using the chi-square test. Results: The CBS c.844ins68 allele is present in six of the seven populations analyzed, and allele frequencies range from 1.5% in Balija to 9.1% in Sugali populations. The CBS c.844ins68 polymorphism showed a significant protective effect on NSCLP at both genotype (WW versus WI: odds ratio [OR] = 0.54, 95% confidence interval [CI] = 0.31 to 0.95, P = .149) and allele levels (W versus I: OR = 0.56, 95% CI = 0.32 to 0.96, P = .033). Conclusions: The current study observed significant differences in the frequency of the CBS 844ins68 allele across populations. There is a significant association between CBS c.844ins68 polymorphism and cleft lip and palate in the Indian population. Additional studies are warranted to identify the functional variants in the genes controlling homocysteine as etiological contributors to the formation of oral clefts.